(untitled) (Bangladesh Journal of Medical Science, 2026)
Background Gastrostomy is widely used to provide long-term enteral nutrition for children with severe nutritional disorders. However, the optimal method of gastrostomy placement remains controversial, as each method has its advantages and potential complications. In recent years, percutaneous endoscopic gastrostomy (PEG) has gained increasing popularity due to its minimally invasive nature. The aim of this study was to compare the clinical outcomes and complications associated with different gastrostomy techniques and to evaluate the safety of a modified Push-PEG method. Methods A retrospective single-center study included 120 pediatricpatients who underwent gastrostomy placement using four different techniques: open gastrostomy (OG), laparoscopic gastrostomy (LG), standard Push PEG, and modified Push- PEG. Patient demographics, operative time, length of hospital stay, indications for gastrostomy, and postoperative complications were analyzed. Statistical analysis was performed to compare outcomes between the groups. Results The main indication for gastrostomy placement was dysphagia (75%), followed by malnutrition (25%). The overall complication rate was 42.5%. No significant differences were found between the groups in the rate of minor complications (p = 0.630). However, significant differences were observed for major complications, with the highest rates seen after open and laparoscopic gastrostomy, and the lowest after the modified Push-PEG technique (p = 0.001). Conclusions The modified Push-PEG technique is a safe and minimally invasive alternative to surgical gastrostomy methods, reducing operative time, accelerating recovery, and decreasing the risk of major postoperative complications in pediatric patients. Bangladesh Journal of Medical Science Vol. 25 No. 03 July’26 Page: 880-886